The REDUCTION OF TRAFFIC LOAD IN CLOUD COMPUTING USING ENERGY EFFICIENT CLUSTERING TECHNIQUE - Sateesh Nagavarapu, Vamsi KrishnaK.Bhavani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
: Cloud computing data centres have grown in popularity recently for the supply of diverse computer resources. Reduced power usage is becoming a major concern for many data centres. Because of its ability to minimise the workload on data centres while also lowering overall energy consumption, the clustering approach in cloud computing is unsurpassed. In this paper, the focus is on energy efficiency and reducing load, and various energy efficiency and load balancing techniques are used to reduce the load at different data centres.